Exploring English Learning Challenges among Culinary Students: An English for Specific Purposes Perspective - Ni Putu Lindawati; Retny Asriyani (LPPM Universitas Dhyana Pura, 2026)
English communication skills have become increasingly important for culinary professionals due to the growing interaction between the culinary industry and international communities. However, many culinary students still experience difficulties in developing English competence that supports their academic activities and future workplace communication. This study aimed to investigate the challenges experienced by culinary students in learning English from English for Specific Purposes (ESP) perspective. This research employed a descriptive mixed-method approach involving fourteen Diploma 1 Culinary students at Akademi Komunitas MAPINDO. Data were collected through questionnaires and semi-structured interviews to identify students perceived difficulties and learning experiences. The questionnaire data were analyzed using descriptive statistics (frequencies and percentages), while the interview data were analyzed using thematic analysis to identify recurring themes. The findings reveal that students faced several challenges, particularly in culinary-related vocabulary mastery, speaking confidence, pronunciation, and limited exposure to contextualized English learning materials. The study highlights the importance of implementing ESP-based instruction that integrates culinary contexts and workplace communication activities. The findings provide practical implications for English instructors in developing more relevant learning strategies and materials for culinary education.